2011
DOI: 10.1002/j.1532-2149.2011.00037.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the neonatal clinical risk for illness severity influence pain reactivity and recovery in preterm infants?

Abstract: The infants exhibiting a high neonatal clinical risk showed high arousal during the puncture procedure and higher physiological reactivity in the recovery phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
1
8
0
1
Order By: Relevance
“…Pain is under-notified, not systematically assessed through validated instruments, poorly documented in medical charts, and, consequently, undertreated, in both developed (Stevens et al, 2011;Taylor, Boyer, & Campbell, 2008) and developing countries (Linhares et al, 2012). The prevalence, assessment, and management of pediatric pain was examined in a Brazilian public teaching hospital, with the findings providing evidence of the high prevalence of pain in pediatric inpatients and the under-recognition of pain by health professionals (Linhares et al, 2012). In this Brazilian audit study, with 34 children/adolescents interviewed, 59% reported pain, 68% of whom reported that they received pharmacological intervention for pain relief.…”
Section: Mbm Linhares and CM Gaspardomentioning
confidence: 99%
See 2 more Smart Citations
“…Pain is under-notified, not systematically assessed through validated instruments, poorly documented in medical charts, and, consequently, undertreated, in both developed (Stevens et al, 2011;Taylor, Boyer, & Campbell, 2008) and developing countries (Linhares et al, 2012). The prevalence, assessment, and management of pediatric pain was examined in a Brazilian public teaching hospital, with the findings providing evidence of the high prevalence of pain in pediatric inpatients and the under-recognition of pain by health professionals (Linhares et al, 2012). In this Brazilian audit study, with 34 children/adolescents interviewed, 59% reported pain, 68% of whom reported that they received pharmacological intervention for pain relief.…”
Section: Mbm Linhares and CM Gaspardomentioning
confidence: 99%
“…The clinical health status of the newborn is directly associated with gestational age and birth weight, with increased lengths of stay in NICU related to more painful procedures in the neonatal pain history (Goffaux et al, 2008;Valeri, Gaspardo, Martinez, & Linhares, 2012;Williams, Ktattak, Garza, & Lasky, 2009). The inpatients of the NICU are mainly preterm and very low birth weight newborns with clinical diseases associated, such as intracranial hemorrhage, bronchopulmonary dysplasia, and/or retinopathy of prematurity.…”
Section: Mbm Linhares and CM Gaspardomentioning
confidence: 99%
See 1 more Smart Citation
“…Preterm neonates show cortical (1,2), biochemical (3), physiological (4,5), and behavioral (6,7) responses to painful procedures. Nonpharmacological management has been recommended for pain relief, such as nonnutritive sucking (8), breastfeeding (9,10), skin-to-skin contact (11,12), and sweetened solutions, including glucose (13), fructose (14), and sucrose (15-19).…”
Section: Introductionmentioning
confidence: 99%
“…Assim, o desenvolvimento inicial do bebê nascido pré-termo pode sofrer impactos negativos decorrentes dos fatores que caracterizam a UTIN como um ambiente estressor, a saber: procedimentos invasivos e dolorosos (Valeri, Holsti, & Linhares, 2015), sons altos (Lahav & Skoe, 2014), alta luminosidade (Morag & Ohlsson, 2016), multiplicidade de estímulos táteis (Gaspardo, Chimello, Cugler, Martinez, & Linhares, 2008), e separação da mãe (Mooney-Leber & Brummelte, 2017). O estado clínico do recém-nascido é diretamente associado à idade gestacional e peso ao nascer, com o aumento do tempo de internação na UTIN e a procedimentos mais dolorosos na história de dor neonatal (Goffaux et al, 2008;Valeri, Gaspardo, Martinez e Linhares, 2012;Williams, Ktattak, Garza, & Lasky, 2009). O desenvolvimento inicial e posterior da criança nascida prétermo pode sofrer danos em decorrência dessa experiência inicial de dor e estresse neonatal (Grunau, 2013;Valeri et al, 2015).…”
Section: Os Contextos De Desenvolvimento E a Unidade De Terapia Intenunclassified